Effect of Aspartame on the Rat’s Thyroid Gland: A histological and Morphometrical Study - Nali Abdulkader Maaruf; Zana Mustafa Mahmood; Paiman Jamal Muhamad Amen (Diyala Journal of Medicine, 2018)
Background: The aspartame is a synthetic sweetener has been used for many purposes as an anti-inflammatory agent, antioxidants and hepato protective, its metabolites can be toxic to many organs and several studies on laboratory animals have been made to verify aspartames toxicity which can cause harmful effect after administration for long duration at a dose of 150 mg/kg body weight.